Perilaku Politik Masyarakat Suku Jawa dalam Pemilihan Kepala Desa (Studi Kasus Desa Bandar Klippa Kecamatan Percut Sei Tuan) - Saparudin Brutu; Berliana Grace Devali Sianturi; Putri Andini; Julia Ivanna (Departement of Mathematics Education, 2024)
This research explores the political behavior of the Javanese community in Bandar Klippa Village in the village head election, especially the Javanese community but the reality of the problem is still very thick with the problem of Javanese cultural traditions, this still dominates as a national culture and tradition in Indonesia. The election of the village head in Bandar Klippa Village reflects the dynamics of the political behavior of the Javanese community which is influenced by factors that influence the political behavior of the Javanese community such as mutual cooperation and togetherness, traditional customs and values, community economic conditions, attractiveness of economic programs, level of education, criticism and rationalism, influence of community leaders and local elites, family influence, access and influence of social media, campaigns through traditional media, community views on community political behavior in the election of the village head. So that this research uses qualitative which is intended to describe the phenomenon of what is experienced by the research subject in the form of perceptions, actions and behavior which are then described in the form of descriptions, and the techniques used in qualitative research using interviews to obtain sources (informants) from the community around Bandar Klippa.